Heavy metal contamination of soils in China: standards, geographic distribution, and food safety considerations. A review - Delang, Claudio O. (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
This article reviews the conditions of heavy metal contamination of China’s soils. The article starts with a discussion of the official environmental standards of soils in China, in terms of heavy metal contamination, and the extent of that contamination. Then, the article discusses the geographic distribution of soil contamination, and the food safety impact. The problem in China is that the provinces with the highest rates of soil contamination are also provinces with the largest amount of food production. This results in high contamination of food, with 13.86 % of grain produced in China being affected by heavy metal contamination. Hunan Province represents the worst conditions: it is responsible for 32.1 % of China’s cadmium (Cd) emissions, 20.6 % of its arsenic (As) emissions, 58.7 % of its mercury (Hg) emissions, and 24.6 % of its lead (Pb) emissions. While Hunan Province produces about 15 % of the total rice output of the country, according to official data, 13 % of the total area of the province has been contaminated with waste and heavy metals from mines. In many areas, especially those closer to mines, the agricultural production exceeds the official food safety standards.